2020
DOI: 10.1016/j.envpol.2020.113987
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium distribution in mature durum wheat grains using dissection, laser ablation-ICP-MS and synchrotron techniques

Abstract: Understanding how essential and toxic elements are distributed in cereal grains is a key to improving the nutritional quality of cereal-based products. The main objective of this work was to characterize the distribution of Cd and of nutrients (notably Cu, Fe, Mn, P, S and Zn) in the durum wheat grain. Laser ablation inductively coupled mass spectrometry and synchrotron micro X-ray fluorescence were used for microscale mapping of Cd and nutrients. A dissection approach was used to quantitatively assess the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…Concentrations of Cu, Pb, and Zn concentrations in wheat samples (Table 1; Supplemental Table S3) were similar to those found in earlier works (e.g., Cardoso et al., 2018; Cubadda et al., 2005; Giordano & Blandino, 2018; Yan et al., 2020). Pearling, or the removal of wheat bran, also affected heavy metal distribution in different wheat grain fractions (Table 1; Supplemental Table S3).…”
Section: Discussionsupporting
confidence: 88%
“…Concentrations of Cu, Pb, and Zn concentrations in wheat samples (Table 1; Supplemental Table S3) were similar to those found in earlier works (e.g., Cardoso et al., 2018; Cubadda et al., 2005; Giordano & Blandino, 2018; Yan et al., 2020). Pearling, or the removal of wheat bran, also affected heavy metal distribution in different wheat grain fractions (Table 1; Supplemental Table S3).…”
Section: Discussionsupporting
confidence: 88%
“…The results that Cd was fully bound to S in the nodes, the majority of Cd in the grains was bound to S ( Figure 4b ), and no isotope fractionation occurred between the node, panicle, and grains ( Figure 3B ) suggest that Cd was transported as Cd–S from the nodes into the grains. A transport from the node to the grain without ligand exchange would require that Cd is transported as Cd–S complex from the node via phloem directly into the grain crease ( Yan et al, 2020 ). Little is known how Cd and metals are transported from the nodes into the phloem.…”
Section: Discussionmentioning
confidence: 99%
“…This observation coincides with previously published size exclusion ICP-MS data that identified S-bearing proteins as the major storage form of Cd in rice ( Wei et al, 2017 ). In addition, μXANES studies revealed that large fractions of up to 92% of Cd can be bound to S in rice and wheat grains ( Gu et al, 2020 ; Yan et al, 2020 ). The consistent findings that S can be an important binding site for Cd may have implications on Cd absorption in human nutrition ( Gu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Cd 2+ not only causes renal tubular dysfunction and bone degeneration (itai-itai disease), [4][5][6] but is also classied as a carcinogenic chemical by the International Agency for Research on Cancer (IARC). [7][8][9] Traditionally, inductively coupled plasma mass spectrometry (ICP-MS), 10,11 atomic absorption spectrometry (ABS) [12][13][14] and ion chromatography 15,16 are used for detecting Cd 2+ . Although these instruments have good precision and high resolution, they are too expensive and laborintensive.…”
Section: Introductionmentioning
confidence: 99%